Design of differential microstrip ring antenna - Cheong, Kai Xiang (Nanyang Technological University, 2021)
Microstrip antennas have been widely studied and used for many years. It has many advantages like being light, small size and easy to fabricate which traditional antennas cannot offer. In recent years, the differential microstrip antenna has been gaining popularity for its low noise, low interference and being a solution to a single chip in radio systems. These characteristics eliminates the use of a lossy Balun which usually comes together with single ended microstrip antennas.